Effects of Different Slope Construction Methods on the Behaviour of Soil Using Finite Element Method (FEM) - Yeoh , Jun Jie (Universiti Teknologi PETRONAS, 2018)
Slope stability problems is important as the failure of the slopes would not only lead to the destruction of the site, but also endanger lives. Many landslides incident in the world is caused by human activities. In current practice, there are two types of slope construction, which is through embankment and excavation. Although both methods are widely used in the construction field, there is a lack of information on the differences of soil behaviour due to both methods. This study focusses on the the behaviour of slope due to different slope construction methods, which is embankment slope and excavated slope. The differenes in soil displacement, stresses and FOS of slope is studied by the application of Finite Element Method (FEM) with PLAXIS 2D software. The differences of soil behaviour for both construction methods are then compared in this study. This study can help engineers to understand the differences better and further help in design and decision making.